Experimental and theoretical studies of (FTIR, FT-NMR, UV-Visible, X-ray and DFT) 2-(4-Allyl-5-pyridin-4-yl-4H-[1,2,4]triazol-3-ylsulfanyl)-1-(3-methyl-3-phenyl-cyclobutyl)-ethanone - Ataol, Cigdem Yuksektepe; Ekici, Oner (Elsevier, 2014)
The single crystal structure, 2-(4-Allyl-5-pyridin-4-yl-4H-[1,2,4]triazol-3-ylsulfanyl)-1-(3-methyl-3-phenyl-cyclobutyl)-ethanone, has been synthesized and characterized by IR, NMR, UV spectra and X-ray diffraction methods. In addition, the optimized structure, the vibrational assignments, the chemical shifts, the molecular orbital energies, molecular electrostatic potential maps and thermodynamic properties, ionization potential, electron affinity, electronegativity, global chemical hardness and chemical softness of the molecule have been investigated by using Density Functional Theory with B3LYP/6-31G(d) and B3LYP/6-311G(d, p) basis sets. UV-Visible spectrum of the compound was recorded and the electronic properties HOMO and LUMO energies were measured by time-dependent TD-DFT approach. The observed results of the compound have been compared with theoretical results and it is found that the experimental data show good agreement with calculated values. The single crystal structure of the compound crystallizes in the monoclinic system with space group C 2/c. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Pyridin; Triazole; Single crystal; Density Functional Theory; Vibrational assignment